Respuesta :
Answer:
x(x+3)(x-3)
Step-by-step explanation:
Factor out common term x
=x(x^2-9)
Factor x^2-9;
(x+3)(x-3)
=x(x+3)(x-3)
Answer:
x(x + 3)(x - 3)
Step-by-step explanation:
What we're given is a difference of squares multiplied by x. If we start by factoring x out, we can simply expand the binomial:
x³ - 9x
= x(x² - 9)
= x(x + 3)(x - 3)
Any time you see an expression in the format a² - b², that is called a difference of squares, and can always be expanded out to (a + b)(a - b). In this case, a is x, and b is 3.